(untitled) (International Seven Journal of Health Research, 2024)
The uterine cervix, also known as the cervix, is the lower and narrower part of the uterus, establishing the connection between the vaginal canal and the internal organs of the female reproductive system. This type of cancer is mostly associated with persistent infection by the Human Papillomavirus (HPV) and is the third most common type of cancer among women. The role of the nursing professional is crucial in the process of detecting and diagnosing cervical neoplasia. Nursing actions include advising the population on the importance of regular preventive examinations. The aim of this study is to analyze the importance of health education in the context of the cytopathological examination, exploring the relationship between health education and the performance of this examination. Methodologically, this is an integrative literature review, using the following databases: PUBMED, SCIELO and BVS, using the following descriptors: "cytopathological examination", and "pap smear", "health education", and "patient adherence". A total of 120 articles were found and 11 were selected for analysis based on the inclusion and exclusion criteria. It was concluded that raising awareness about testing is essential and should be done with humanized care and proximity to the woman. Health education is a tool that should be used by the entire multi-professional team. Its benefits include the dissemination of quality information to more people, increased demand for health services, counseling, thus reducing the incidence of cervical cancer, early diagnosis and effective treatment of these patients.